Wage Differences According to Workers' Origin: The Role of Working More Upstream in GVCs - Valentine Fays; Benoît Mahy; Francois Rycx (Institute of Labor Economics (IZA), 2021)
This paper is the first to investigate the role of firm-level upstreamness (i.e. the number of steps before the production of a firm meets final demand) in explaining wage differences according to workers' origin. Using unique linked employer-employee data relative to the Belgian manufacturing industry for the period 2002-2010, our estimates show that firms that are further up in the value chain pay significantly higher wages. However, the wage premium associated with upstreamness is also found to vary substantially depending on the origin of the workers. Unconditional quantile estimates suggest that those who benefit the most from being employed in more upstream firms are high-wage workers born in developed countries. In contrast, workers born in developing countries, irrespective of their earnings, appear to be unfairly rewarded. Quantile decompositions further show that, while differences in average values of upstreamness according to workers' origin play a limited role, differences in wage premia associated with upstreamness account for a substantial part of the wage gap between workers born in developed and developing countries, especially at the top of the earnings distribution. These results are shown to be robust to a number of sensitivity tests, including broader or narrower definitions of workers' wages and different firm environments in terms of technological and knowledge intensity.
Keywords: J15; J31; F16; 330; wage gaps; workers' origin; global value chains; upstreamness; unconditional quantile estimates and decompositions